Knowledge and Opinions of Third Year Veterinary Students Relevant to Animal Welfare Before and After Implementation of a Core Welfare Course - Johnstone, Elizabeth C. S.; Frye, Melinda A.; Lord, Linda K.; Baysinger, Angela K.; Edwards-Callaway, Lily N. (Frontiers in Veterinary Science, 2019)
Although leading veterinary organizations emphasize the importance of animal welfare knowledge, there exists a gap in current veterinary student animal welfare education and training. A survey instrument was created to assess third-year Doctor of Veterinary Medicine (DVM) student knowledge of key animal welfare topics, opinions regarding the inclusion of welfare education in the veterinary curriculum, and views on veterinarian responsibilities as advocates. In Spring 2018, Colorado State University added a required animal welfare course to the DVM curriculum. Pre- and post-course paper surveys were distributed to the third-year students enrolled in the animal welfare course. One hundred thirty one completed pre-course surveys were collected and 125 completed post-course surveys were collected. Of the pre and post-course surveys collected, 61 were paired with identification codes and utilized for statistical comparison. Results indicated that the course led students to view the inclusion of an animal welfare course in the veterinary curriculum more favorably (p = 0.009) and improved their confidence in conducting research on animal welfare topics (p < 0.001). The course did not change students' sense of responsibility toward welfare advocacy. Associations were not found between attitudes toward these issues and demographic variables of home community, respondent gender, and track selection (p > 0.06). Veterinarians were consistently ranked by students as the most influential member of a community in matters of animal welfare. Future research on the lack of veterinary student knowledge of animal welfare should be done on a national scale to facilitate strategic development of mandatory animal welfare courses in veterinary curricula. Future research should be designed to gain knowledge regarding DVM students' opinions and attitudes regarding effective methods of incorporating animal welfare education into their professional training.